2004
DOI: 10.1128/jcm.42.5.2294-2297.2004
|View full text |Cite
|
Sign up to set email alerts
|

Culture-Independent Species Typing of Neotropical Leishmania for Clinical Validation of a PCR-Based Assay Targeting Heat Shock Protein 70 Genes

Abstract: PCR-restriction fragment length polymorphism analysis of heat shock protein 70 genes discriminates most neotropical Leishmania species, as well as Trypanosoma cruzi. The assay, combined with capillary electrophoresis in a microchip device, may be applied directly on clinical samples with a high sensitivity, hence supporting clinical and epidemiological monitoring of leishmaniasis

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
166
0
26

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 187 publications
(196 citation statements)
references
References 10 publications
4
166
0
26
Order By: Relevance
“…Various studies have suggested the usefulness of molecular techniques for the aetiological diagnosis of ATL (Pirmez et al 1999, de Oliveira et al 2003, Schonian et al 2003, Garcia et al 2004, Marques et al 2006, Gomes et al 2008, Luz et al 2009). In different studies conducted on humans, the sensitivity of the polymerase chain reaction (PCR) was about 100%, whereas 60% was observed for other types of exams.…”
mentioning
confidence: 99%
“…Various studies have suggested the usefulness of molecular techniques for the aetiological diagnosis of ATL (Pirmez et al 1999, de Oliveira et al 2003, Schonian et al 2003, Garcia et al 2004, Marques et al 2006, Gomes et al 2008, Luz et al 2009). In different studies conducted on humans, the sensitivity of the polymerase chain reaction (PCR) was about 100%, whereas 60% was observed for other types of exams.…”
mentioning
confidence: 99%
“…Con el protocolo diseñado por García, et al (11), se han reportado nuevas restricciones enzimáticas basadas en la misma PCR, que permitieron distinciones aún no registradas de especies o grupos de especies. Así, se propusieron nuevas enzimas para distinguir entre las especies predominantes en Brasil, fundamentalmente del subgénero L. (Viannia) (23), y otras para identificar especies no estudiadas con anterioridad procedentes del Nuevo o del Viejo Mundo (15).…”
Section: Discussionunclassified
“…En este contexto, la variante PCR-hsp70/RFLP basada en el gen hsp70, propuesta por García, et al (11), y modificada posteriormente, detecta 14 especies de importancia médica usando un solo par de cebadores y, a partir de un único producto de amplificación, logra identificar individualmente la mayoría de dichas especies mediante una o dos restricciones enzimáticas (15). Esta variante se ha aplicado tanto al análisis de cepas como al de muestras clínicas humanas (16).…”
Section: Molecular Identification Of Leishmania Spp In Clinical Isolunclassified
See 1 more Smart Citation
“…22,28,29,33,[62][63][64] The sensitivity varies according to the PCR protocol used, but in all cases, PCR proved to be more sensitive and specific in detecting Leishmania parasites compared with culture, microscopy, or clinical diagnosis (especially for ML). Similar to parasite culture, however, the use of PCR in Bolivia is limited to research purposes or epidemiologic studies because of the cost and need for specialized laboratory infrastructure and technically trained staff.…”
Section: Disease Distribution Notification and Incidencementioning
confidence: 99%